A Single-Phase H-Bridge Buck Inverter with Common-Ground Ability - Hoàng Minh Đạt; Trần Vĩnh Thanh; Danh Quang Huy; Đỗ Đức Trí (Journal of Technical Education Science, 2024)
This paper presents a new single-phase inverter configuration capable of suppressing common-mode voltage (CMV) called a single-phase H-bridge buck inverter with common-ground ability (1P-H-CGI). The 1P-H-CGI configuration is built on a buck-boost DC-DC converter with two additional semiconductor switches to enable the inverter function (DC-AC). In this design, the ground of the DC input source is directly connected to the negative point of the output load. Therefore, this configuration can completely eliminate leakage current as well as CMV. In addition, the proposed configuration has a low voltage across the power elements and the use of film capacitors makes the inverter more efficient and reliable than previous common-ground inverter configurations. To verify the theoretical basis presented in the paper on operating modes, modulation algorithms, as well as performance of the 1P-H-CGI configuration, simulation and experimental results were performed with the support of PSIM, PLECS software, and experimental models in the laboratory. The small signal model of the proposed configuration is also considered and analyzed in this paper.